2012
DOI: 10.3133/sir20125240
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations, loads, and yields of select constituents from major tributaries of the Mississippi and Missouri Rivers in Iowa, water years 2004-2008

Abstract: Excess nutrients, suspended-sediment loads, and the presence of pesticides in Iowa rivers can have deleterious effects on water quality in State streams, downstream major rivers, and the Gulf of Mexico. Fertilizer and pesticides are used to support crop growth on Iowa's highly productive agricultural landscape and for household and commercial lawns and gardens. Water quality was characterized near the mouths of 10 major Iowa tributaries to the Mississippi and Missouri Rivers from March 2004 through September 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 11 publications
1
40
0
Order By: Relevance
“…3). Model bias was computed for WRTDS TN and TP concentration models by comparing the sum of estimated concentrations on days when samples were collected to the sum of measured sample concentrations for each site, similar to methods described in Stenback and others (2011), and used in Garrett (2012), Sprague and others (2011), and Sprague and Gronberg (2013). The absolute bias in the nitrogen and phosphorus WRTDS models was not greater than 3.3 percent at any site (table 2).…”
Section: Annual Flow-normalized Total Nitrogen and Total Phosophorus mentioning
confidence: 99%
“…3). Model bias was computed for WRTDS TN and TP concentration models by comparing the sum of estimated concentrations on days when samples were collected to the sum of measured sample concentrations for each site, similar to methods described in Stenback and others (2011), and used in Garrett (2012), Sprague and others (2011), and Sprague and Gronberg (2013). The absolute bias in the nitrogen and phosphorus WRTDS models was not greater than 3.3 percent at any site (table 2).…”
Section: Annual Flow-normalized Total Nitrogen and Total Phosophorus mentioning
confidence: 99%
“…Ninety-five percent confidence intervals around estimated mean annual loads and FWCs quantify uncertainty around estimates and generally were larger for constituents with greater variability in measured loads (tables 4 and 5). Recent research has shown that LOADEST models can produce biased estimates of long-term average constituent loads (Stenback and others, 2011;Garrett, 2012;Hirsch, 2014), and LOADEST has since been modified to facilitate residual analysis and bias identification (Runkel, 2013). Long-term bias in model estimates was less of a concern because the modeling period was only 3 years and predictor variables describing trends in time were not used.…”
Section: Load Estimation (Loadest) Model Resultsmentioning
confidence: 99%
“…This type of model has been used to estimate constituent concentrations for periods when sample data were not available (Gilroy and others, 1990), and to estimate a basin flux of water-quality constituents (Goolsby and others, 1999). Additional predictor variables describing streamflow variability were tested for significance in LOADEST models according to methods described by Garrett (2012).…”
Section: Loadest Models For Estimating Constituent Loadsmentioning
confidence: 99%
“…The explanatory variable dQ k was evaluated to represent streamflow variability or hysteresis and is described in Garrett (2012). Hysteresis occurs when the value of a physical property (constituent concentration or load) changes at a different rate than the effect assumed to be causing it (streamflow).…”
Section: Sediment Streamflow Surrogate Analysismentioning
confidence: 99%
“…Use of a streamflow hysteresis term might eliminate the need to develop a different regression between streamflow and load depending on whether samples were collected on the rising or the falling limb of the hydrograph. The streamflow hysteresis term was defined as the difference between mean streamflow (Q) on day i and the mean streamflow of the previous k days, given as equation 8 but described in more detail in Garrett (2012):…”
Section: Sediment Streamflow Surrogate Analysismentioning
confidence: 99%